2020
DOI: 10.1002/marc.202000438
|View full text |Cite
|
Sign up to set email alerts
|

Triblock Copolymer/Polyoxometalate Nanocomposite Electrolytes with Inverse Hexagonal Cylindrical Nanostructures

Abstract: The primary issue of polymer electrolytes is to achieve high ion conductivity while retaining mechanical properties. A nanocomposite electrolyte with the inverse hexagonal cylindrical phase (three‐dimensionally continuous domains for ion conduction and embedded domains for mechanical support) is prepared through the electrostatic self‐assembly of a polyoxometalate (H3PW12O40, PW) and a triblock copolymer poly(N‐vinyl pyrrolidone)‐block‐polystyrene‐block‐poly(N‐vinyl pyrrolidone) (PSP). The cylindrical nanocomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 52 publications
(88 reference statements)
0
18
0
Order By: Relevance
“…We found that the conductivities of PGP8-30, PGP17-23, and PGP23-30 at 353 K are increased from 7.6, 18.2 to 32.7 mS cm −1 , accompanied by a decreased activation energy from 0.16, 0.13 to 0.12 eV by Arrhenius fitting (Figure 5c and Table 1), respectively, which corresponds to a Grotthuss-type proton conduction mechanism. 60 The contents of PW in PGP8-30, PGP17-23, and PGP23-30 are all 30 wt % and thus lead to the same IEC of 0.31 mmol g −1 . Given this situation, the enhanced conductivities and the decreased E a from PGP8-30, PGP17-23 to PGP23-30 should be ascribed to the improved connectivity of PW networks but not the IEC.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…We found that the conductivities of PGP8-30, PGP17-23, and PGP23-30 at 353 K are increased from 7.6, 18.2 to 32.7 mS cm −1 , accompanied by a decreased activation energy from 0.16, 0.13 to 0.12 eV by Arrhenius fitting (Figure 5c and Table 1), respectively, which corresponds to a Grotthuss-type proton conduction mechanism. 60 The contents of PW in PGP8-30, PGP17-23, and PGP23-30 are all 30 wt % and thus lead to the same IEC of 0.31 mmol g −1 . Given this situation, the enhanced conductivities and the decreased E a from PGP8-30, PGP17-23 to PGP23-30 should be ascribed to the improved connectivity of PW networks but not the IEC.…”
Section: Resultsmentioning
confidence: 97%
“…[48][49][50] Recently, the excellent proton conductivity, electrochemical stability, and water-retention ability of POMs have attracted special interest to develop POM-polymer composite electrolytes for proton conduction. [51][52][53][54][55][56][57][58][59][60][61] However, it is difficult to manipulate the distribution of POMs in polymer electrolytes to form well-connected proton conductive pathways, as the strong electrostatic interaction easily induces the disordered aggregation of POMs. Recently, Guiver and co-workers reported a breakthrough they obtained: one-dimensional (1D) POM-based protonconducting channels in a homopolymer electrolyte matrix through an external magnetic field alignment.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the hybrid material was unstable in high ionic strength media due to the weakened electrostatic interactions between the POM and polymer, which limited the application of these compounds in the field of bio-imaging and bio-detection. 15 as electrostatic crosslinkers to form bicontinuous 41 inverse hexagonal 42 and lamellar morphologies 43 with the positively charged polymer poly(styrene-b-2-vinylpyridinium) (PS-b-P2VP). These nanocomposites exhibited enhanced proton conductivity and mechanical strength as the result of using macroions as functional additives.…”
Section: Additives In Polymeric Materialsmentioning
confidence: 99%
“…The extent of polymerisation was shown to impact the POM sensitized emission. 40 The group of Haolong Li used [PW 12 O 40 ] 3À and [SiW 12 O 40 ] 4À (P3) as electrostatic crosslinkers to form bicontinuous 41 inverse hexagonal 42 and lamellar morphologies 43 with the positively charged polymer poly(styrene-b-2-vinylpyridinium) (PS-b-P2VP).…”
Section: Additives In Polymeric Materialsmentioning
confidence: 99%
See 1 more Smart Citation